Bankruptcy of PT Nyonya Meneer in Bankruptcy Law Perspective: Facing Challenges of Cultural Heritage Business Protection - Zaenuri, Zaenuri; Juwita , Juwita (CV. Publikasi Indonesia, 2025)
This study aims to analyze the implications of PT Nyonya Meneer's bankruptcy on the protection of cultural heritage and the sustainability of the national herbal medicine industry. This study uses a normative juridical approach by examining the relationship between bankruptcy law, cultural law, and intellectual property law. The results of the study show that the application of bankruptcy law is still economically oriented and has not considered cultural values in the asset settlement process. As a result, the bankruptcy of PT Nyonya Meneer not only caused economic losses, but also led to the loss of traditional knowledge and cultural identity. This study found that there is a normative gap between Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations (PKPU) and Law of the Republic of Indonesia Number 5 of 2017 concerning Cultural Advancement, so that a culturally insightful reformulation of bankruptcy law is needed. The reformulation is directed to integrate economic, social, and cultural aspects so that bankruptcy law can function as an instrument to protect national heritage while supporting sustainable economic development.